Evaluation of Selected Inquiry Skills of Future Biology Teachers - Čipková, Elena; Fuchs, Michael (Scientia in educatione, 2021)
Scientific research is a systematic way of gaining scientific knowledge. It covers not only the use of scientific methods and procedures but also processes associated with the development of scientific knowledge such as asking questions, creative problem solving, studying of various information sources, critical thinking, scientific reasoning, sharing and defending the conclusions. The successful application of scientific research in science education requires adequate professional training of teachers. This fact increases the demands on the preservice biology teachers’ preparation in terms of supporting the development of inquiry skills. In this article, we present the results of research aimed at evaluating the current level of inquiry skills of student teachers in combination with the subject of biology at the Faculty of Natural Sciences, Comenius University in Bratislava. The results of the research show that future biology teachers do not have sufficiently developed inquiry skills, especially skills associated with planning and conducting an experiment.